Parenthood: Contributions from Psychoanalysis to Public Health Policies - Katia Tarouquella Brasil; Eliana R. Lazzarini; Daniela Scheinkman; Marcia Maesso; Sandra Baron; Viviane Legnani; Didier Drieu (Psicologia: Teoria e Pesquisa)
Abstract The article aims to discuss the relevance of attention to parenthood in public health policies, considering that official documents related to pregnancy, birth and the first bonds of the baby are still lacking on the theme of mental health. It presents, from the conceptual operators proposed by psychoanalysis, the training guidelines for professionals in the public health network. It highlights the use of active methodologies in this training process, in order to promote a critical and reflective posture of these professionals on the importance of promoting a significant bond of the baby with his parental environment so that it can prevent intrafamily violence.